2016
DOI: 10.3390/min6010016
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Permeability of Round Top Mountain Rhyolite (Texas, USA) Favor Coarse Crush Size for Rare Earth Element Heap Leach

Abstract: Water-saturation porosity and dye-penetration permeability measurements of Round Top Mountain rhyolite confirm that a ½-inch (13-mm) crush size would permit efficient acid heap leaching of yttrium and heavy rare earth elements (YHREEs) hosted in yttrofluorite, a YHREE-substituted variety of fluorite. Laboratory acid leaching has extracted up to 90% of the YHREEs. The bulk insoluble gangue mineralogy of the rhyolite, 90% to 95% quartz and feldspars, assures low acid consumption. Different crush sizes were weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…This porosity is evident in the mineral maps. Using ArcGIS™, the percentage of pore spaces was calculated to range from 1.4% to 4.0% in the 7 samples, consistent with earlier measurements of porosity by water saturation [5].…”
Section: Mineralogical Textural Analysis: Porositysupporting
confidence: 82%
See 1 more Smart Citation
“…This porosity is evident in the mineral maps. Using ArcGIS™, the percentage of pore spaces was calculated to range from 1.4% to 4.0% in the 7 samples, consistent with earlier measurements of porosity by water saturation [5].…”
Section: Mineralogical Textural Analysis: Porositysupporting
confidence: 82%
“…Previous studies have shown that Round Top Mountain rhyolites have 1% to 2% porosity in the gray varieties and 3% -8% porosity in the pink varieties [5].…”
Section: Mineralogical Textural Analysis: Porositymentioning
confidence: 93%
“…Because the deposit is exposed at the surface there is little overburden to be excavated before surface mining could begin. Furthermore, the Round Top rhyolite has proved both porous and permeable, making high leach YHREE recoveries, up to 90%, possible without fine grinding [26]. It also is important to note that the YHREEs at Round Top present a compact, 3-dimensional mining opportunity.…”
Section: Introductionmentioning
confidence: 99%
“…After performing extensive laboratory tests, Texas Mineral Resources Corporation has proposed to extract the YHREEs via a heap leach with dilute H 2 SO 4 [27] [28] [29]. The YHREE host yttrofluorite was found to be soluble in dilute sulfuric acid, a relatively inexpensive and widely available industrial chemical.…”
Section: Introductionmentioning
confidence: 99%